Navigating the Journey: A Qualitative Study of Indonesian Muslim Fathers' Experiences in Raising Children with Autism Spectrum Disorder - Masykur, Achmad Mujab; Nawangsari, Nur Aini Fardana; Wiwin, Hendriani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
The number of families raising children with autism spectrum disorder (abbreviated as ASD) is increasing, attributed to the expansion of diagnostic practices and increased awareness of autism. Research related to fathering children with ASD, is still dominated by Western society, often neglecting the realities experienced by fathers from non-Western societies. This research aims to deeply understand the experiences of muslim fathers raising children with ASD in Indonesia. A total of five Muslim fathers participated in this study. The sample size provides sufficient power to yield in-depth qualitative insights into the nuances of the challenges they face in their experience as fathers through detailed interviews. The data were analyzed using a thematic model, and four main themes were identified, reflecting Muslim fathers' experiences in raising children with ASD. The themes are: 'It's Just the Beginning,' highlighting the initial challenges; 'The Impact of Having a Child with ASD,' which explores emotional, physical and social repercussions; 'Focus on Advocating for Children,' indicating their active role in fulfilling children's rights; and 'Life Must Go On,' emphasizing resilience to continue living despite facing challenges. Each theme is interconnected, revealing the profound journey these fathers navigate. The characteristics of fathers, religion, education level, social value systems, culture, and the severity level of the child's condition Influence the fathers' experiences in raising children with ASD. This study encourages greater inclusion of religious and cultural considerations in discussions about fathering children with autism, serving as a basis for developing support systems and interventions.